DEVELOPMENT OF MATHEMATICS LEARNING MEDIA FOR RECOGNIZING FLAT SHAPES FOR GRADE VII STUDENTS WITH MILD INTELLECTUAL DISABILITIES IN SPECIAL EDUCATION SCHOOLS - Dwi Endah Pertiwi; Fajar Indra Septiana; Eka Yuli Astuti; Emay Mastiani; Widi Pratiwi (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2023)
Children with mild intellectual disabilities experience limitations in their cognitive abilities, which can impact their academic performance, particularly in subjects such as mathematics. To facilitate comprehension for these children, it is essential to use concrete and engaging learning media. This study aims to assess the effectiveness of such media in aiding children with disabilities in learning mathematics. The research employs a descriptive qualitative method. The findings reveal that some children with mild intellectual disabilities are able to recognize geometric shapes with teacher guidance, although others continue to face challenges. The study concludes with the development of validated mathematics learning media designed to help Grade VII students with mild intellectual disabilities recognize geometric shapes using Geoboard media. The study recommends that schools provide educational props or support media to enhance mathematics instruction related to data structures. It is also suggested that teachers and parents integrate these media into every lesson for practical application, with the goal of continuous improvement in the accessibility and effectiveness of learning media for children with mild intellectual disabilities.